A Behavioral Addiction Model of Revenge, Violence, and Gun Abuse. Issue 4 (December 2020) - Kimmel, James; Rowe, Michael
Data from multiple sources point to the desire for revenge in response to grievances or perceived injustices as a root cause of violence, including firearm violence. Neuroscience and behavioral studies are beginning to reveal that the desire for revenge in response to grievances activates the same neural reward-processing circuitry as that of substance addiction, suggesting that grievances trigger powerful cravings for revenge in anticipation of experiencing pleasure. Based on this evidence, the authors argue that a behavioral addiction framework may be appropriate for understanding and addressing violent behavior. Such an approach could yield significant benefits by leveraging scientific and public health-oriented drug abuse prevention and treatment strategies that target drug cravings to spur development of scientific and public-health-oriented "gun abuse" prevention and treatment strategies targeting the revenge cravings that lead to violence. An example of one such "motive control" strategy is discussed. Approaching revenge-seeking, violence, and gun abuse from the perspective of compulsion and addiction would have the added benefit of avoiding the stigmatization as violent of individuals with mental illness while also acknowledging the systemic, social, and cultural factors contributing to grievances that lead to violent acts.